Plant Growth and Photosynthetic Characteristics of Mesembryanthemum crystallinum Grown Aeroponically under Different Blue- and Red-LEDs - He, Jie; Qin, Lin; Chong, Emma L. C.; Choong, Tsui-Wei; Lee, Sing Kong (Frontiers in Plant Science, 2017)
Mesembryanthemum crystallinum is a succulent, facultative CAM plant. Plant growth and photosynthetic characteristics were studied when M. crystallinum plants were grown indoor under LED-lighting with adequate water supply. Plants were cultured aeroponically for a 16-h photoperiod at an equal photosynthetic photon flux density (PPFD) of 350 µmol m-2 s-1 under different red:blue LED ratios: 1) 100:0 (0B); 2) 90:10 (10B); 3) 80:20 (20B), 4) 70:30 (30B), 5) 50:50 (50B) and 6)100:0 (100B). M. crystallinum grown under 10B condition had the highest shoot and root biomass and shoot/root ratio while those grown under 0B condition exhibited the lowest values. Compared to plants grown under 0B condition, all other plants had similar but higher total chlorophyll (Chl) and carotenoids (Car) contents and higher Chl a/b ratios. However, there were no significant differences in Chl/Car ratio among all plants grown under different red- and blue-LEDs. Photosynthetic light use efficiency measured by photochemical quenching (qP) and non-photochemical quenching (NPQ) and electron transport rate (ETR), demonstrated that plants grown under high blue-LED utilized more light energy and had more effective heat dissipation mechanism compared to plants grown under 0B or lower blue-LED. Statistically, there were no differences in photosynthetic O2 evolution rate, light-saturated CO2 assimilation rate (Asat), and light-saturated stomatal conductance (gs sat) among plants grown under different combined red- and blue-LEDs but they were significantly higher than those of 0B plants. No statistically differences in total reduced nitrogen (TRN) content were found among all plants. For the total soluble protein, all plants grown under different combined red- and blue-LEDs had similar values but they were significantly higher than that of plants grown under 0B condition. However, plants grown under higher blue-LEDs had significant higher Rubisco protein than those plants grown under lower blue-LED. High Asat and gs sat but very low CAM acidity of all M. crystallinum plants during light period, imply that this facultative CAM plant performed C3 photosynthesis when supplied with adequate water. Results of this study suggest that compared to red or blue-LED alone, appropriate combination of red- and blue-LED lighting enhanced plant growth and photosynthetic capacities of M. crystallinum.